Факторний і дискримінантний аналіз інформаційного поля парамерів адаптації та імунітету і неспецифічного захисту - Попович, І.Л.; Церковнюк, Р.Г.; Гучко, Б.Я. (Медична гідрологія та реабілітація, 2005)
Методом факторного анализа осуществлена конденсация информации о состоянии приспособительно-защитных систем лиц с дизадаптозом и иммунодисфункцией, а методом дискриминантного анализа отобраны параметры, характерные для определенного типа общей адаптационной реакции организма. By using methods of factor analysis it is made condensation of information about state of adaptive and defensive systems the patients with dysadaptose and immunodysfunction. By using methods of discriminant analysis it is selected parameters characterising types of general adaptativ reactions.